Meaning Properties of Covid-19 Related Terms in Selected Articles - Fita Chyntia; Deliana Deliana; Umar Mono (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
This study aims to see the meaning properties of the Covid-19 terms in six different articles. By seeing the meaning properties of these Covid-19 terms we can find if the terms are used meaningfully in those articles. The basis of meaning properties include being meaningful or meaningless – they are deemed meaningless if the words used contain ambiguity, redundancy, anomaly, and contradiction. In this study, the qualitative method was used. The sources of data are covid-19 related articles from Google Scholar. The articles chosen are free-accessed articles related to covid-19 impacts, pandemic, and its measures to tackle the crisis. The six covid-19 related articles are read through and the covid-19 related words or phrases that occur more than one time in one article and in more than one article are collected as the data, thirty-eight terms are the result of this data collection. The application of the thirty-eight terms is analyzed by their meaning properties. The result shows there are nine phrases or sentences that are anomalies, five redundancies, and two ambiguities in the original articles. The findings show that even in Google Scholar articles, some of the Covid-19 terms are not used meaningfully in the sentences.